2021
DOI: 10.1111/ijd.15656
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐laminin‐γ1 pemphigoid in an epitope spreading phenomenon, successfully treated with rituximab

Abstract: Anti-laminin-c1 pemphigoid in an epitope spreading phenomenon, successfully treated with rituximab Dear Editor, Anti-laminin-c1 pemphigoid, also known as anti-p200 pemphigoid, is a rare subepidermal autoimmune blistering disorder with binding of autoantibodies (AAbs) to the dermal side on indirect immunofluorescence (IIF) microscopy. Other blistering disorder with binding of AAbs to the dermal side of salt-split skin includes epidermolysis bullosa acquisita (EBA), mucous membrane pemphigoid (MMP), cicatricial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was further confirmed that direct immunofluorescence using a biopsy of lesioned skin of the left leg showed no IgG, IgA, IgM and complement C3 deposition at the basement membrane zone or on keratinocyte cell surfaces. This patient's serum showed negative IgG, IgA and IgM results on indirect immunofluorescence using normal human skin and indirect immunofluorescence using salt-split skin (22,23). According to ELISAs using commercially available kits (Medical and Biological Laboratories, Co., Ltd.), IgG autoantibodies against Dsg1, Dsg3, BP180, BP230 and COL7 were all negative.…”
Section: Resultsmentioning
confidence: 88%
“…It was further confirmed that direct immunofluorescence using a biopsy of lesioned skin of the left leg showed no IgG, IgA, IgM and complement C3 deposition at the basement membrane zone or on keratinocyte cell surfaces. This patient's serum showed negative IgG, IgA and IgM results on indirect immunofluorescence using normal human skin and indirect immunofluorescence using salt-split skin (22,23). According to ELISAs using commercially available kits (Medical and Biological Laboratories, Co., Ltd.), IgG autoantibodies against Dsg1, Dsg3, BP180, BP230 and COL7 were all negative.…”
Section: Resultsmentioning
confidence: 88%